Kontribusi Di Air Terjun Tancak Kembar Bondowoso - Hutama, Pandu Satriya; Prasetyan, Salsabyla; Hasan, Wildan; Candrawinata, Riandra Dwi; Firmansyah, Alvin Wahyu; Yahya, Achmad Zakariya (International Conference on Multidisciplinary Issues (INCOMI), 2024)
The Tancak Kembar waterfall in Bondowoso, Indonesia, is a natural wonder with two parallel streams that create a stunning view on the slopes of Mount Raung. The calm atmosphere and cool air make it a popular destination for peace seekers. Surrounded by tropical forests, visitors can enjoy the beauty of nature, listen to birds chirping, and feel the fresh mountain air. Our group identified the economic, environmental and visitor aspects of Tancak Kembar Waterfall. And our group also highlighted deficiencies, including the condition of the facilities